2005
DOI: 10.1002/app.21626
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of methyl methacrylate onto sodium alginate initiated by potassium ditelluratoargentate(III)

Abstract: Sodium alginate (SA) was graft-copolymerized with methyl methacrylate in an alkali aqueous solution with potassium ditelluratoargentate(III) (DTA) as the initiator. Graft copolymers with both a high grafting efficiency (Ͼ90%) and a high percentage of grafting were obtained, which indicated that the DTA-SA redox pair was an efficient initiator for this grafting. The grafting parameters, including total conversion, grafting efficiency, and percentage grafting, were evaluated comparatively. The dependence of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
6
12
0
Order By: Relevance
“…In addition, the decrease in the monomer‐to‐backbone ratio also accounted for the observed decrease in % G . Similar observations have also been reported earlier …”
Section: Resultssupporting
confidence: 93%
“…In addition, the decrease in the monomer‐to‐backbone ratio also accounted for the observed decrease in % G . Similar observations have also been reported earlier …”
Section: Resultssupporting
confidence: 93%
“…Similar results were found for the graft copolymerization of acrylamide onto cellulose with ceric ammonium nitrate. 17 Liu et al 18 studied the grafting of methyl methacrylate onto another polysaccharide sodium alginate with potassium ditelluratoargentate(III). They reported the same trend for the effect of the reaction time on the grafting parameters.…”
Section: Effect Of the Polymerization Timementioning
confidence: 99%
“…Similar results have been obtained by many workers who have studied graft copolymerization. [18][19][20][21] Zhang and Tan 19 studied the graft copolymerization of 2-(dimethylamino)ethyl methacrylate onto carboxymethylated cellulose and reported that the grafting parameters increased with an increase in the temperature up to 358C and then decreased up to 608C.…”
Section: Effect Of the Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Grafting of vinyl monomers onto alginate and other natural polysaccharides through free radical polymerization has attracted the interests of many researchers and scientists in the last two decades (Liu, Yang, Li, & Shi, 2005;Osemeahon, Barminas, Aliyu, & Nkafamiya, 2008;Sirlatha & Rao, 2007). This technique enables the production of new hybrid polymer materials with desired properties (Fakhru'L-Razi et al, 2001;Patel, Patel, & Trivedi, 1999;Pourjavadi, Hosseinzadeh, & Mazidi, 2005).…”
Section: Introductionmentioning
confidence: 99%